2007
DOI: 10.1080/13694670600668291
|View full text |Cite
|
Sign up to set email alerts
|

Measuring attitude toward Judaism: The internal consistency reliability of the Katz–Francis Scale of Attitude toward Judaism

Abstract: This paper describes and discusses the development and empirical properties of the 24-item Likert-type Katz-Francis Scale of Attitude toward Judaism. The scale is designed to facilitate inter-faith comparisons within the psychology of religion alongside the well-established Francis Scale of Attitude toward Christianity. Data are provided from a sample of 618 Hebrew-speaking undergraduate students attending Bar-Ilan University. The findings confirm the reliability of the scale and commend it for further use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
9

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 105 publications
3
48
0
9
Order By: Relevance
“…Application of the Sahin-Francis Scale of Attitude toward Islam Revised can facilitate the integration of research findings generated within an Islamic context alongside studies that have utilised the Francis Scale of Attitude toward Christianity (Francis, Lewis, Philipchalk, Brown, & Lester, 1995), the Santosh-Francis Scale of Attitude toward Hinduism (Francis, Santosh, Robbins, & Vij, 2008) and the Katz-Francis Scale of Attitude toward Judaism (Francis & Katz, 2007). In this way the empirical psychologies of religion evolving across different religious traditions may be more effectively brought into the dialogue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of the Sahin-Francis Scale of Attitude toward Islam Revised can facilitate the integration of research findings generated within an Islamic context alongside studies that have utilised the Francis Scale of Attitude toward Christianity (Francis, Lewis, Philipchalk, Brown, & Lester, 1995), the Santosh-Francis Scale of Attitude toward Hinduism (Francis, Santosh, Robbins, & Vij, 2008) and the Katz-Francis Scale of Attitude toward Judaism (Francis & Katz, 2007). In this way the empirical psychologies of religion evolving across different religious traditions may be more effectively brought into the dialogue.…”
Section: Resultsmentioning
confidence: 99%
“…It stands alongside the Katz-Francis Scale of Attitude toward Judaism (Francis & Katz, 2007) and the Santosh-Francis Scale of Attitude toward Hinduism (Francis, Santosh, Robbins, & Vij, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In the second study in the series, Francis and Katz (2007) reported the development of the Katz-Francis Scale of Attitude toward Judaism. In this case the 24 items of the Francis Scale of Attitude toward Christianity were recast in ways accessible for Hebrew-speaking Jews living in Israel.…”
Section: Astley-francis Scale Ofattitude Toward Theistic Faithmentioning
confidence: 99%
“…Some of the scales of attitude to religion seem more readily applicable to non-Christian religions than others. One style of attitude measure which has proved valid and reliable for religiosity in Christianity (Francis 1978), Hinduism (Francis et al 2008), Islam (Sahin & Francis 2002) and Judaism (Francis & Katz 2007) is that of the Francis Scale of Attitude toward Christianity (FSAC). In brief, it has employed attitude questions on religious values using a five-point Likert scale, to yield a score of between the extremes of 24 (negative attitude) and 120 (positive attitude).…”
Section: Introductionmentioning
confidence: 99%